The effects of specific surface area and ash on char gasification mechanisms in the mixture of H2O, CO2, H2 and CO. (1st December 2017) - Zhang, Rui; Chen, Yifan; Lei, Kai; Liu, Dong
Highlights: The char gasification mechanism is influenced by the specific surface area of char. The gasification mechanism is influenced by the ash of char. The separate and common active sites assumptions of char gasification can be unified. Abstract: The gasification mechanism of char in the mixture of H2 O, CO2, H2 and CO is controversial for a long time, and the reasons leading to different results of validation experiments of gasification mechanism are yet not clear. In this study, the specific surface area (SSA) and ash of char are assumed to be the possible reasons leading to the controversial results. The large-SSA char, the small-SSA char, and the ash-free char were prepared for validation experiments. The gasification experiments were performed in the mixture of H2 O, CO2, H2 and CO using a modified TGA system. The experimental results indicate that SSA and ash really have significant effects on char gasification mechanism. The gasification mechanism of large-SSA char is close to the separate active sites assumption, while the gasification mechanism of small-SSA char is close to the common active sites assumption. The gasification mechanism will transition from the separate active sites assumption to common active sites assumption if the ash is removed from the large-SSA char, and will become closer to the separate active sites assumption again if Na is loaded to the ash-free char. Therefore, for char gasification in the mixture of H2 O, CO2, H2 and CO, the separate and common active sites assumptions are two extreme situations of the same gasification mechanism. Finally, a unified model was proposed based on this char gasification mechanism. This model is applicable to the char samples that have different specific surface areas and ash contents.